Special paperCoronary computed tomography angiography in planning of percutaneous coronary interventions in bifurcation lesions – study design and rationale - Wolny, Rafał; Pręgowski, Jerzy; Witkowski, Adam (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Percutaneous treatment of coronary bifurcations is a complex issue due to numerous possible techniques and high risk of complications. Because of increasing interest in non-invasive imaging in interventional cardiology and growing quality of obtained images, we designed a prospective, randomized, single-blinded trial to evaluate the role of coronary computed tomography angiography (CCTA) in the planning of percutaneous coronary interventions (PCI) of bifurcation lesions. Eighty eligible patients scheduled for PCI of bifurcations in stable coronary artery disease will undergo additional CCTA examination and will be randomized 1 : 1 to either planning of PCI using angiography and CCTA or to PCI planning with use of angiography alone. Primary endpoints will include PCI strategy (one or two stents), technique, size of implanted stents and direct angiographic effect of the procedure. Immediate PCI effect measured with intravascular ultrasound (IVUS) and the effect on fractional flow reserve (FFR) in the side branch (in a subgroup of patients), as well as plaque morphology assessed in CCTA, patient radiation exposure and amount of contrast will be compared in secondary analysis. The study is intended to clarify the influence of CCTA analysis on the technique and direct effect of PCI of bifurcations and to provide evidence on the relevance of performing a CCTA scan prior to PCI of bifurcation lesions.